FAKTOR INDIVIDU, ORGANISASI, DAN SISTEM TERHADAP SIKAP PENGGUNA E-BANKING - Heri Setiawan (Jurnal Keuangan dan Perbankan, 2013)
The study investigated the influence of individual, organizational and system factors on attitude amongelectronic banking users in Palembang, Sumatera Selatan. The five constructs were system and service quality,perceived risk, organizational reputation, perceived ease of use and perceived usefulness on attitude whichwere used to determine users to use e-banking. Survey research design was adopted. Seven hundred and fiftysix e-banking users in four banks were selected using Stratified Random Sampling. Data were collected usinga structured questionnaire. Frequency and percentage distributions and multiple regressions were measuredusing analytical techniques. The research hypotheses were tested at 0.05% level of significance. Findingsrevealed that the constructs system and service quality, perceived risk, organizational reputation, perceivedease of use and perceived usefulness had a significant influence on the attitude of e-banking users. It wasconcluded that individual, organizational and systems factors influenced attitude toward use of e-banking.Banks should have made the interface of e-banking systems as friendly as possible and adopted the latesttechnologies that were standardized for effective and efficient e-banking transactions.